The Role of the Village Government in Increasing Agricultural Product (MIDACENG) in Mattirowalie Village Mare District Bone Regency - Asriadi Asriadi; Zainal Zainal; Abdul Rahman; Mardi Mardi (Program Pascasarjana Universitas Negeri Makassar, 2022)
Clove is one of the crops that have high selling value in Indonesia. Almost all components of this clove plant can be used, including the clove leaf itself. This study aims to determine the role of the village government and the factors that influence the increase in the agricultural product (Midaceng). The method of this research was descriptive with a qualitative approach. Research data was collected through structured interview techniques. The data analysis techniques used data reduction, data presentation, and conclusion drawing. The results of this study indicate that the Mattiro Wallie Village Government plays an active role in supporting the condition of natural resources, establishing a clove leaf distillation factory, establishing cooperation between the government and the community, and improving the welfare of the community. The factors that support the increase in clove leaf oil production are internal factors like Human Resources (HR), the lack of infrastructure such as clove leaf storage warehouses, and Marketing Techniques for Production Results (Clove Leaf Oil). Meanwhile, external factors include natural factors (weather), lack of local government participation in seeing opportunities from clove leaf oil processing, business capital, and communication problems (networks).